Effects of fish-derived protein hydrolysate, animal-based organic fertilisers and irrigation method on the growth and quality of grape tomatoes. Issue 2 (3rd April 2021) - García-Santiago, Juana Cruz; Lozano Cavazos, Carlos Javier; González-Fuentes, José Antonio; Zermeño-González, Alejandro; Rascón Alvarado, Emilio; Rojas Duarte, Alfonso; Preciado-Rangel, Pablo; Troyo-Diéguez, Enrique; Peña Ramos, Fidel Maximiano; Valdez-Aguilar, Luis Alonso; Alvarado-Camarillo, Daniela; Hernández Maruri, José Alfredo
ABSTRACT: Agriculture needs to supply food for a growing population whilst also minimising the environmental impact, and the adoption of sustainable agriculture systems has been proposed as a solution to achieve this. The objective of this study was to evaluate the effects of seven fertilisation treatments (FT1-FT6 organic fertilisers, FT7 conventional fertiliser) and two irrigation methods (drenching and non-recirculating subirrigation (NRS)) on plant growth, yield, fruit quality and polyphenol concentrations in grape tomatoes. For plants irrigated by drenching, leaf dry weight (dw), total plant biomass dw, fruit number and total yield were higher in the organic fertilisation treatment FT6 (including fish-derived protein hydrolysate as an N-source), surpassing the conventional treatment (FT7) by 35%, 9%, 21%, and 4% for these parameters, respectively, though the difference was only significant for leaf dw. For plants grown with NRS, the total yield in FT7 was higher than that in any of the organic fertiliser treatments. In the organic treatments FT1, FT3 and FT4 the tomatoes had higher total soluble solids concentrations than the fruit in FT7. With drench irrigation, the concentrations of total hydrolysable polyphenols were highest in FT2, FT5 and FT7, but with NRS, it was highest is FT2. With drenching, the concentration of total condensed polyphenols was highest in FT1, whereas with NRS it was similar in all fertilisation treatments. The results indicated that for the production of grape tomatoes, adding fish-derived protein hydrolysates and using the subirrigation system can help reduce the gap between the yields of organic and conventional systems.